Afrikanischer Urbanismus – Sind afrikanische Städte “anders”? - Krüger, Fred (Modulør : Architektur, Immobilien, Recht, 2023)

Children, Adolescents and the HIV and AIDS Pandemic: Changing Inter-Generational Relationships and Intra-Family Communication Patterns. - Geiselhart, Klaus; Krüger, Fred; Gwebu, Thando (Children, Youth and Environments, 2008)
The HIV and AIDS pandemic has become an omnipresent part of everyday life in Botswana. Children grow up to be teenagers and young adults and have to adapt to the devastating conditions created by the HIV and AIDS crisis. Based on theoretical concepts of risk and vulnerability and on qualitative empirical research, this article inquires into the relations between children and their guardians in Botswana. The research shows that families in Botswana have insufficient strategies to educate children about important issues concerning adolescence and HIV and AIDS. The results also indicate that children experience inter-generational conflicts, insecure livelihoods, and are torn between different explanations of HIV and AIDS. However, children are not simply victims; they are also able to cope actively.
UnivIS-Import:2015-04-14:Pub.2008.nat.dgeo.IG.profes.childr
Keywords: HIV; AIDS; people living with HIV and AIDS; PLWHA; risk; vulnerability; resilience; communication; orphans; Botswana

Culturally sensitive public health makes a difference: The HIV/AIDS disaster and beyond - Krüger, Fred; Geiselhart, Klaus; Schmitz, Peter (World Disasters Report 2014. Focus on culture and risk, 2014)
Cultures perceived as integral parts of fields of practices, as commitments, agendas and actions, may coexist in a local setting, but not necessarily in harmony. They may collide, or be contested or ignored, and people or organizations whose actions are framed by different cultures might suffer from the consequences of these contests. The example of HIV/AIDS-related research in Botswana is used to explain the implications this has for public health and to illustrate the perspective, in this chapter, of culture and health. Many individuals who work in public health and in disaster management, or who are directly affected by calamitous health-related events, have observed that, in public health and humanitarian assistance evolving around HIV/AIDS, local nurses and other medical personnel have a good understanding of the needs and hardship of those living with HIV and AIDS. They are, however, often restricted in their actions by conditions governed at higher levels of their institutions.
Keywords: HIV; AIDS; risk; culture; public health; traditional medicine; DRR

Cultures and Disasters: Understanding Cultural Framings in Disaster Risk Reduction - Krüger, Fred; Bankoff, Greg; Cannon, Terry; Orlowski, Benedikt Marko; Schipper, Lisa (Routledge, 2015)
Why did the people of the Zambesi Delta, affected by severe flooding, return early to their homes or even choose to not evacuate? How is the forced resettlement of small-scale farmers living along the foothills of an active volcano in the Philippines impacting on their day-to-day livelihood routines? Making sense of such questions and observations is only possible by understanding how the decision making of societies at risk is embedded in culture, and how intervention measures acknowledge, or neglect, cultural settings. The social construction of risk is being given increasing priority in the understanding of how people experience and prioritise hazards in their own lives and how vulnerability can be reduced, and resilience increased, at a local level. Cultures and Disasters adopts an interdisciplinary approach to explore the cultural dimension of disaster with contributions from leading international experts in the field. Section I provides a discussion of research in both theoretical and practical considerations to better understand the importance of culture in hazards and disaster management. Culture can be interpreted widely with many different perspectives; this enables us to critically consider the culturally-bound nature of research itself as well as the complexities of incorporating various interpretations into Disaster Risk Reduction (DRR). If culture is omitted from consideration, related issues of adaptation, coping, intervention, knowledge and power relations cannot be fully grasped. Section II explores what aspects of culture shape resilience and how people use culture in everyday life to establish DRR practice. It looks at what constitutes a resilient culture and what role culture plays in a society’s decision making. It is natural for people to seek refuge in tried and trusted methods of disaster mitigation; however, cultural and belief systems are constantly evolving. How these coping strategies can be introduced into DRR therefore poses a challenging question. Finally, Section III examines the effectiveness of key scientific frameworks for understanding the role of culture in DRR and management. DRR includes a range of norms, and breaking these through improved cultural understanding will challenge established theoretical and empirical frameworks.

Das subsaharische Afrika: Entwicklungsdynamiken, Herausforderungen, Lösungsversuche - Krüger, Fred; Drescher, Axel; Louis, Norman; Titz, Alexandra (Geographische Rundschau, 2019)
In recent years, the pace and multiplicity of development dynamics in Sub-Saharan Africa has increased such that new explanatory approaches are needed to assess the spatial, economic and social transformation and propose adequate solutions to tackle poverty and vulnerability. Demographic scenarios indicate that Sub-Saharan societies will have to face a wide range of challenges in the coming decades. European development policies, Chinese economic intervention, or a new African urbanism serve as examples to highlight the diverse transformation that is currently affecting everyday livelihoods in Sub-Saharan Africa.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Human Development Index (HDI); Globaler Süden; fragmentierende Entwicklung; HDI; Human Development Index

Environmental management and the reshaping and respacing of livelihoods in sub-Saharan Africa: a short commentary on recent trends and conceptual ideas - Krüger, Fred; Samimi, Cyrus (African Geographical Review, 2019)
In recent years, many regions in sub-Saharan Africa have experienced growing contestations of existing livelihood practices and massive environmental change.This has been accompanied by what has sometimes been described as a 'respacing' of Africa, i.e. an increasing blurriness of the nation state and social relationships becoming more and more interconnected on the local to global scales, rendering conventional concepts of space and territory obsolete. In this introductory essay, we briefly discuss notions of this 'respacing' process, highlight its validity but also its ambiguity, and thus lay the ground for the ensuing compilation of papers on social, environmental, and spatial change in sub-Saharan Africa.
CRIS-Team WoS Importer:2019-06-18

Infrastrukturentwicklung und das Recht auf Stadt: Das Beispiel Daressalaam - Munishi, Emmanuel; Louis, Norman; Drescher, Axel; Krüger, Fred (Geographische Rundschau, 2019)
Im Kontext der urbanen Transformation im subsaharischen Afrika finden Möglichkeiten der Ordnung und Steuerung von Stadtentwicklung zwar zunehmende Beachtung. Fragen zur aktiven Mitgestaltung von Stadt durch ihre Bewohnerschaft bleiben aber meist noch unberücksichtigt. Das Projekt AfriCity am Institut für Geographie der Friedrich-Alexander-Universität Erlangen-Nürnberg untersucht die Wechselbeziehungen zwischen Umweltveränderungen, Ressourcennutzung und Recht-auf-Stadt-Prozessen in afrikanischen Städten südlich der Sahara. In der tansanischen Küstenmetropole Daressalaam ist eine Gerechtigkeitsperspektive für aktuelle Prozesse des städtischen Umbruchs relevant, da die jüngsten Transformationsprojekte dort weitreichende Auswirkungen z. B. auf städtische Straßenverkäufer hatten.<br
CRIS-Team Scopus Importer:2019-12-10
Keywords: Ostafrika; Tansania; Umsiedlung

The bus rapid transit (BRT) in Dar es Salaam: A pilot study on critical infrastructure, sustainable urban development and livelihoods - Krüger, Fred; Titz, Alexandra; Arndt, Raphael; Gross, Franziska; Mehrbach, Franziska; Pajung, Vanessa; Suda, Lorenz; Wadenstorfer, Martina; Wimmer, Laura (Sustainability, 2021)
Inner-city transportation looms large in big cities in the so-called Global South due to rapid population and urban growth. To tackle this challenge, a Bus Rapid Transit (BRT) system was implemented in Dar es Salaam (Tanzania) in 2016. This paper reports on the results of a pilot study on the impacts of the BRT on city development and livelihoods in Dar. Our pilot study, which is part of the collaborative research project LIPSINDAR (Linking Partners for a Sustainable and Inclusive Dar es Salaam), was not designed to provide a comprehensive insight into the problems of urban planning, infrastructure modification and their impact on urban livelihoods. Rather, using the example of Dar es Salaam, the study served as an entry point to highlight challenges and future research demands in the context of urban insecurities and risks in large cities of the Global South. In particular, our study investigated the BRT as an element of critical infrastructure in Dar es Salaam and probed into its impact on residents’ livelihoods, focusing on the influence of service disruptions on everyday routines, and on different stakeholders’ views on the functionality of the BRT. Elaborating on this topic, interviews, street vendor surveys and mappings were used as methods to describe the processes. To examine the results more closely, the outcome was divided into groups of different fields of activity, namely Traffic Management, Local Residents, City Administration, Basic Provision Services and Street Vendors. In summary, the pilot study confirms that the implementation of the BRT system has, in general, served to improve urban livelihoods. Reducing commuting times and enhancing access to basic services found positive results. There is, however, still potential for improvement: the bus network, in particular, needs to be expanded and the vulnerability to natural extreme events, especially flooding, needs to be addressed.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Critical infrastructure; Criticality; Eastern Africa; Inclusiveness; Infrastructure; Livelihoods; Risk; Society; Sub-saharan Africa; Sustainability; Transportation; Urban resilience

The cultural sense of disasters: Practices and singularities in the context of HIV/AIDS - Geiselhart, Klaus; Schlatter, Fabian; Orlowski, Benedikt Marko; Krüger, Fred (Cultures and Disasters: Understanding Cultural Framings in Disaster Risk Reduction, 2015)
Defining a disaster is a cultural act: naming a disaster first starts with recognising societal conditions that are evaluated to be disastrous. Plainly, this can only be done in reference to values and norms. In a second stage, conditions tagged as disastrous become traced to either a hazardous event or to social circumstances and dealings that have reduced people’s resilience, rendered them vulnerable, or hampered their appropriate response to threats. It is thus intelligible that in different cultures, depending on particular perceptions and values, disasters can be substantially different things. Disaster definitions, for example, are created by organisations, institutions or individuals with regard to their own practical assignments. But, then, how can ‘a culture’ be identified, a situation be narrowed down to a ‘disaster’, and appropriate disaster risk reduction (DRR) measures be initiated?
Keywords: Risk; Disaster; Culture

The HIV/AIDS crisis - Botswana's strategic answer as a role model? - Geiselhart, Klaus; Krüger, Fred (Geographische Rundschau, 2007)
Southern Africa is severely hit by the HIV and AIDS pandemic. Botswana leads the list of high prevalence countries. Since 2002, the government of Botswana provides free antiretroviral therapy for all eligible HIV and'AIDS patients. The article describes the HIV/AIDS background and the ARV programme. It explores why this ARV-scheme, although sophisticated und successful, may have only limited potential to serve as a role model. In Botswana medical infrastructure had already been well established and served as an entry point for ARV schemes. Also, political and economic "good governance" helped in gaining international support. However, the new social transformation processes induced by the ARV programme need to be monitored closely.

The myth of community? - Titz, Alexandra; Krüger, Fred; Cannon, Terry; et al. (World Disasters Report 2014. Focus on Culture and Risk, 2014)

Uncovering "Community': Challenging an Elusive Concept in Development and Disaster Related Work - Titz, Alexandra; Cannon, Terry; Krüger, Fred (Societies, 2018)
In all areas of academic or practical work related to disaster risk, climate change and development more generally, community and its adjunct community-based have become the default terminology when referring to the local level or working with the people'. The terms are applied extensively to highlight what is believed to be a people-centred, participatory, or grassroot-level approach. Today, despite, or because of, its inherent ambiguity, community' tends to be used almost inflationarily. This paper aims to analyse the way the concept of community' has come into fashion, and to critically reflect on the problems that come with it. We are raising significant doubts about the usefulness of community' in development- and disaster-related work. Our approach is to first consider how community' has become popular in research and with humanitarian agencies and other organisations based on what can be considered a moral licence' that supposedly guarantees that the actions being taken are genuinely people-centred and ethically justified. We then explore several theoretical approaches to community', highlight the vast scope of different (and contested) views on what community' entails, and explain how community' is framing practical attempts to mitigate vulnerability and inequity. We demonstrate how these attempts are usually futile, and sometimes harmful, due to the blurriness of community' concepts and their inherent failure to address the root causes of vulnerability. From two antagonistic positions, we finally advocate more meaningful ways to acknowledge vulnerable people's views and needs appropriately.
Created from Fastlane, WoS look-up

USA Regional: Der Mittlere Westen - Dynamische Veränderungen im Herzen der USA - Fuchs, Stephan; Gerhard, Ulrike; Krüger, Fred; Titz, Alexandra (Geographische Rundschau, 2015)

USA regional: Mythos und Alltagskultur – der Mittlere Westen - Krüger, Fred; Titz, Alexandra (Kulturgeographie der USA - Eine Nation begreifen, 2017)
Bereits in der unscharfen Bezeichnung „Mittlerer Westen“ kommen die zumeist eher diffusen und räumlich schwer abgrenzbaren Vorstellungen vom großen Zentralraum der Vereinigten Staaten zum Ausdruck. Zwei unterschiedliche Leiterzählungen werden mit diesem Großraum häufig verknüpft: zum einen die Idee des amerikanischen „Heartland“ als Wiege einer von erfolgreicher Agrarkolonisation und Industrialisierung geprägten, kleinbürgerlichen US-amerikanischen Alltagskultur, zum anderen die stark mit mystifizierenden Vorstellungen aufgeladenen Assoziationen der „Frontier“ und des „Wilden Westens“, der von den Great Plains bis über den Mittleren Westen hinaus in die Bergwelten der Rocky Mountains in Wyoming und Montana ausgreift und ebenfalls Bilder des „typisch Amerikanischen“ erzeugt. Beide Meta-Erzählungen produzieren zwar gegenläufige, jedoch gleichermaßen romantisierende, stereotype Vorstellungswelten eines beschaulichen, gutbürgerlichen und fleißigen, im Herzland verorteten Amerika einerseits und einer rauen, von Freiheit, Selbstbehauptung, der Zähmung der Wildnis und der endlosen Weite der Prärie geprägten Lebenswelt andererseits. Geographisch verorten lassen sich diese Fiktionen in erster Linie in den südlichen und westlichen Teilen des Gebiets der Großen Seen (Great Lakes) und in den westlich anschließenden Great Plains. Genau dort finden sich aber auch die realen Gegenbilder dieser Erzählungen: die stark disparaten räumlichen und ökonomischen Entwicklungen in den Teilregionen des Mittleren Westens (Middle West oder Midwest) und die damit einhergehenden dynamischen Veränderungen der Lebenswelte